2018
DOI: 10.1021/acsbiomaterials.8b00626
|View full text |Cite
|
Sign up to set email alerts
|

Microneedles Integrated with ZnO Quantum-Dot-Capped Mesoporous Bioactive Glasses for Glucose-Mediated Insulin Delivery

Abstract: A self-responsive insulin delivery system is highly desirable because of its high sensitivity dependent on blood glucose levels. Herein, a smart pH-triggered and glucose-mediated transdermal delivery system, insulin-loaded and ZnO quantum dots (ZnO QDs) capped mesoporous bioactive glasses (MBGs) integrated with microneedles (MNs), was developed to achieve control and painless administration. ZnO QDs as a promise pH-responsive switch were employed to cap the nanopores of MBGs via electrostatic interaction. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 59 publications
1
59
0
Order By: Relevance
“…Upon exposure to H 2 O 2 , the phenylboronic ester on the surface of the MSNs was oxidized, resulting in the destruction of the host-guest complexation and subsequent release of the preloaded insulin. Recently, mesoporous bioactive glasses was employed as the insulin carrier and integrated with MN device for glucose-responsive insulin delivery [241]. In this design, the porous bioactive glasses loaded with insulin and two enzymes (GOx/CAT) were capped with pH-sensitive ZnO quantum dots as "gatekeepers".…”
Section: Bioresponsive Microneedlesmentioning
confidence: 99%
“…Upon exposure to H 2 O 2 , the phenylboronic ester on the surface of the MSNs was oxidized, resulting in the destruction of the host-guest complexation and subsequent release of the preloaded insulin. Recently, mesoporous bioactive glasses was employed as the insulin carrier and integrated with MN device for glucose-responsive insulin delivery [241]. In this design, the porous bioactive glasses loaded with insulin and two enzymes (GOx/CAT) were capped with pH-sensitive ZnO quantum dots as "gatekeepers".…”
Section: Bioresponsive Microneedlesmentioning
confidence: 99%
“…Since ZnO QDs are dissolvable at a low pH, they can act as pH-sensitive agents (Figure 7). In vivo studies showed the achievement of prolonged moderate blood glucose control by the glucose-responsive MNs, while BGLs dropped quickly when subcutaneous injections were used [134]. Figure 6.…”
Section: Bio-responsive Mnsmentioning
confidence: 99%
“…Amplified glucose levels can effectively diffuse and activate the release of β-cells on the tips of MNs. The amplified signal showed significant effective glucose control for almost 8 h compared with other treatments lacking the live/synthetic part or even with one of the enzymes involved [134]. Bioactive glass nanoparticles (BGN) can be manufactured by BGN soles through gelation under high temperatures.…”
Section: Bio-responsive Mnsmentioning
confidence: 99%
See 2 more Smart Citations